A Discussion of Alexander Cooley and Jack Snyder's Ranking the World: Grading States as a Tool for Global Governance. Issue 1 (15th March 2017) - Rothstein, Bo
Abstract : Ranking the World: Grading States as a Tool of Global Governance, edited by Alexander Cooley and Jack Snyder, assembles an impressive group of political scientists to critically discuss "the important analytical, normative, and policy issues associated with the contemporary practice of 'grading states.'" The volume addresses a topic of importance to a wide range of political scientists in comparative politics, international relations, and political theory, and raises some fundamental questions about the role of political science at the nexus of theory and practice. We have thus invited a number of colleagues to discuss the volume and its broader implications for political science inquiry.